Structure and characteristics of rubberwood - Lim S C; Sulaiman A (Rubberwood Processing and Utilization, Kuala Lumpur, Malaysia, 1994; p17-25, 1994)
The paper presenting a detailed discussion on the anatomy of wood (macroscopic and microscopic analysis) and bark of rubber, formation of tapping panel marks etc. It also discuss with the feature of tension wood in rubber, general characteristics of tension wood and the practical problems associated with the presence of tension wood in utilizing rubber wood for various end uses.
Keywords: Rubberwood